STUDI PERBANDINGAN MOTIVASI BELAJAR ONLINE ANTARA SISWA LAKI-LAKI DAN PEREMPUAN PADA MATA PELAJARAN PPKN DI SMAN 1 KARIMUN - Annisa Azzhara; Gimin Gimin; Separen Separen (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research was motivated by the outbreak of pandemic cases caused by the Corona virus in Indonesia which resulted in learning activities that were usually carried out in schools now being carried out online from home. This research examines the comparison of learning motivation online between male and female students in civic education lessons at public Senior High School 1 Karimun. The formulation of the problem in this research is "Is there a comparison of learning motivation online between male and female students in civic education lessons at public Senior High School 1 Karimun?". To find out the comparison of online learning motivation between male and female students in civic lessons at public Senior High School 1 Karimun is the purpose of this research. This research was carried out at public Senior High School 1 Karimun from July 2021 to September 2021. This research is quantitative descriptive with a population of male and female students in class X majoring in science and social studies at Senior High School 1 Karimun as many as 313 people consisting of 143 male students. and 170 women. The sampling technique is using the method Nonprobability Sampling and the Quota Sampling technique to determine the number of samples using the Yamane formula so that the number of samples is 122 respondents, 59 male students and 63 female students. Data collection instruments are primary data and secondary data obtained through libraries and documentation. The data analysis technique used the analysis Independent Sample T-test with the help of the SPSS version 25 program. Based on the results of the study it was found that there was a comparison of learning motivation online between male and female students in class X majoring in science and social studies in civic lessons at public Senior High School 1 Karimun. It is proven by the results of the calculation with the analysis test Independent Sample T-test where the result of the test is 0.024 and the value is 0.024 < 0.05 (sig. (2-tailed) < 0.05), then Ha is accepted and Ho is rejected. Thus, it can be concluded that there is a comparison of learning motivation online between male and female students in class X majoring in science and social studies in civic education lessons at public Senior High School 1 Karimun.Key Words: : Online Learning Motivation, Comparison, Students, Male, Female